2003
DOI: 10.1038/sj.emboj.7600048
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of ligand recognition by PABC, a highly specific peptide-binding domain found in poly(A)-binding protein and a HECT ubiquitin ligase

Abstract: The C-terminal domain of poly(A)-binding protein (PABC) is a peptide-binding domain found in poly(A)-binding proteins (PABPs) and a HECT (homologous to E6-AP Cterminus) family E3 ubiquitin ligase. In protein synthesis, the PABC domain of PABP functions to recruit several translation factors possessing the PABP-interacting motif 2 (PAM2) to the mRNA poly(A) tail. We have determined the solution structure of the human PABC domain in complex with two peptides from PABP-interacting protein-1 (Paip1) and Paip2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(148 citation statements)
references
References 56 publications
2
145
0
1
Order By: Relevance
“…A closer inspection (Fig. 3A) revealed that the sequence spanning amino acids 161-176 is very similar to PAM2 motifs within PAIP1 and -2 and Ataxin-2 (ATXN2), respectively (46). Yet in MKRN1-short a highly conserved leucine (Leu 128 in PAIP1, Leu 111 in PAIP2, and Leu 913 in ATXN2) is replaced by aspartate (Asp 165 ).…”
Section: Mkrn1 Ismentioning
confidence: 99%
“…A closer inspection (Fig. 3A) revealed that the sequence spanning amino acids 161-176 is very similar to PAM2 motifs within PAIP1 and -2 and Ataxin-2 (ATXN2), respectively (46). Yet in MKRN1-short a highly conserved leucine (Leu 128 in PAIP1, Leu 111 in PAIP2, and Leu 913 in ATXN2) is replaced by aspartate (Asp 165 ).…”
Section: Mkrn1 Ismentioning
confidence: 99%
“…Structural data show that the PAM2 motif binds to the highly conserved MLLE domain in the C-terminal region of PABPC1 (Kozlov et al 2004;Jinek et al 2010;Kozlov and Gehring 2010). Among the PAM2-containing proteins are several well-studied translation and mRNA decay factors, including PAIP1 (Roy et al 2002), PAIP2 (Khaleghpour et al 2001), Tnrc6 (Eystathioy et al 2003), translation termination factor 3 (eRF3) (Hoshino et al 1999), PABP-dependent poly(A) nuclease subunit 3 (Pan3) (Uchida et al 2004), and transducer of erbB-2 proteins (Tob) (Ikematsu et al 1999).…”
Section: Mammalian Cytoplasmic Poly(a)-binding Protein (Pabp)mentioning
confidence: 99%
“…The MLLE/PABC domain is thought to be a protein-protein interaction motif (e.g., known to bind substrates such as PAIP2; refs. 31,32) and may regulate ubiquitin transfer catalyzed by the HECT domain (33).…”
Section: Unique Genomic and Protein Structure Of Ubr5mentioning
confidence: 99%